KAJIAN HADITS TENTANG PERJANJIAN DALAM MEWUJUDKAN PERDAMAIAN PADA PEMBIAYAAN IJARAH MULTIJASA DI LEMBAGA KEUANGAN MIKRO SYARIAH: (Studi Pada KSSU Harum Daha Kediri) (Lembaga Pengembangan Kinerja Dosen, 2023)
In writing this aims to examine the hadith regarding the agreement in realizing peace on Multijasa Ijarah Financing at KSSU Harum Dhaha Kediri. By using a qualitative approach with thematic and interpretive data analysis to gain a comprehensive understanding. The results of the writing show that the Agreement on multiservice ijarah financing at KSSU Harum Dhaha Kediri has an important role in creating peace and justice. With clear, transparent, and fair agreements, the parties involved can carry out their business activities safely and smoothlyIn addition, the agreement refers to the hadith of the Prophet as a source of law governing peace in transactions. The agreement also functions as a risk control instrument and provides a dispute resolution mechanism. Thus, multiservice ijarah financing at KSSU Harum Dhaha Kediri can contribute positively to economic growth based on Sharia values.